Interview - José Augusto Chaves Guimarães - Santarem Segundo, José Eduardo; Almeida, Marco Antonio de; Silva, Márcia Regina da (InCID: Revista de Ciência da Informação e Documentação, 2013)
Entrevista José Augusto Chaves Guimarães